Bijoygarh is one of the most prominent figures in the Settlement and inspiration of refugees/ উদ্বাস্তু উপনিবেশ প্রতিষ্ঠার অনুপ্রেরণার এক অন্যতম উদাহরণ ‘বিজয়গড়’ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
In this article, we shall discuss how East Pakistani refugees established camps and squatter colonies in Calcutta. The colonies struggled to form their own homes. Within the colonies, they established roads, schools, medical facilities, markets, and a rudimentary system of sanitation. Calcutta, being the most important urban centre of this region, perhaps suffered most. The most immediate and difficult problem it faced was the continuous influx of refugees that began in the immediate aftermath of partition and continued for decades. By 1951, refugees coming from East Pakistan and their numbers continued to increase over the years. The early batches of the refugees belonged mostly to the middle class; they were educated and often had some connections with the society started to reach Calcutta in large numbers. The refugees mostly shelter in 24 Parganas, Calcutta, and Nadia. Some other places which become a temporary home for the refugees were Cooch Bihar, Jalpaiguri, and Burdwan. Now I seek highlighted Calcutta’s specified by Bijoygarh. Bijoygarh, was the earliest refugee colony established through ‘Jabardakhal’ in 1948 in an abandoned military barrack in Jadavpur area in the South of Calcutta. There were 149 squatter colonies in and around the cities by the end of 1950. In the next twenty years, another 175 squatter colonies camp up in West Bengal. It is said to have consisted mostly the ‘Bhadrakoks’ or the upper class and upper caste and the only colony which had a college in the year 1954.
Keywords: Partition; Calcutta; East Bengal; Refugees; Squatter’s; Jabardakhal; Other Colonies